A Qualitative Study to Explore Patient’s experiences on Chemotherapy-induced Nausea and Vomiting: Focusing Impact on Daily Life - Gour, Sushil; Kore, Anamika; Das, Abhijit; Dane, Jyoti; Maurya, Rajesh Kumar (Asian Pacific Journal of Cancer Care, 2023)
Background: This study aimed to explore the experience of cancer patients about chemotherapy-induced nausea and vomiting and its effect on patients’ daily life. Methods: A descriptive qualitative study was conducted on cancer patients who experience nausea and vomiting due to chemotherapy. Semi-structured interview guide consisting of eight questions was used as a study tool and thematic analysis was done using QDA Miner lite software. Results: Twenty-five participants were included in the final analysis. The median age of the participants was 53 (IQR-15) years and most of the patients were Hindu. All the patients were newly diagnosed. Approximately 80% of patients had received three cycles of chemotherapy by the time of their interviews. Adriamycin, Cyclophosphamide (AC), Docetaxel (T), Paclitaxel and Carboplatin (P+C) were the chemotherapy drugs administered. Our findings suggest that chemotherapy-induced nausea and vomiting has affected many aspects of patient’s lives, especially those related to eating, physical, emotional, and social functioning, but the degree of impact was unique to each patient. Conclusion: The individual experiences of nausea and vomiting during chemotherapy treatment may have a profound effect on treatment compliance and future outcomes. Specific assessment and innovative approaches for its subsequent management are highly needed while considering the complexity of these symptoms.